Bart’s Syndrome: A rare genetic disorder - Rahman, Muhammad Hasibur; Khan, M Karim; Miah, Md Abdal; Hossain, Md Shahadat (Community Based Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/cbmj.v1i2.13863 Community Based Medical Journal Vol.1(2) 2012 48-50